Is Matter Still A Matter for Undergraduate Students? An Exploratory Study in Indonesia - Putri*, Ananda Hafizhah; Suhandi, Andi; Samsudin, Achmad; Supriyadi, Supriyadi; Cotu, Bayram (Jurnal IPA & Pembelajaran IPA, 2025)
Many studies have focused on students conceptions about the concepts of matter found that students from various levels of education have difficulty in comprehending the states and/or changes of matter. The present study aims to explore undergraduate students conception regarding the states and changes of matter. A total of 16 first to third year university students from physics education and science education department voluntarily participated in the study. We employed semi-structured interviews with each participant in order to elicit students conceptions and alternative conceptions regarding the states and changes of matter. Students were also prompted to make their own molecular illustration during the interview. The present study found that undergraduate students had difficulty in connecting between macroscopic and microscopic concept levels of the states and changes of matter. Furthermore, students developed several alternative conceptions in terms of temperature, volume, mass, and density of an object during phase changes. Undergraduate students also tended to give fewer explanation about transformation on liquid and gas phases due to poor understanding of particulate nature of liquid and gas, molecular bonds in particular. The study suggests the necessity of developing instruction with more contextual learning and the use of dynamic visual media to enhance undergraduate students' comprehensive understanding of the states and changes of matter.